Eficiencia reproductiva de las hembras de Otobius megnini (Acari: Argasidae) - Herrero, Marco V. (Revista de Biología Tropical, 1988)
To evaluate the reproductive efficiency of Otobius megnini (Dugea) females we conducted a study under constant conditions in the laboratory. Mean nutrient weight was 58.9 ± 15.4 mg, nutrient index was 59.6 ± 9.8%, reproductive efficiency index (R. E. I.) was 6.8 ± 1.6 eggs/mg, and the consersion efficiency index (C. E. I) was 277.3 ± 67.4 ug/mg. A positive correlation between egg quantity (number and masa) and nutrient weight was found. Egg laying dynamics was characterized by a preoviposition period of 3.2 ± 1.4 days and an oviposition period of 105.4 ± 18.1 days with 20.0 ± 4.8 ovipositions per female. The total number of eggs per female was 856 ± 225 and the total masa weight per female was 34.6 ± 8.9 mg. The mean egg weight was 43.9 ± 11.0 ug and incubation period was 18.1 ± 2.5 days with 38.95 ± 15.85 percent hatched.